2016
DOI: 10.2967/jnumed.115.167320
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared Diffuse Optical Imaging for Early Prediction of Breast Cancer Response to Neoadjuvant Chemotherapy: A Comparative Study Using 18F-FDG PET/CT

Abstract: Diffuse optical spectroscopic imaging (DOSI) is used as an indicator of tumor blood volume quantified by tissue hemoglobin concentrations. We aimed to determine whether early changes in tumor total hemoglobin (tHb) concentration can predict a pathologic complete response (pCR) to neoadjuvant chemotherapy in patients with operable breast cancer, and we compared the predictive value of pCR between DOSI and 18 F-FDG PET combined with CT. Methods: Of the 100 patients enrolled, 84 patients were prospectively evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 21 publications
(26 reference statements)
2
10
0
Order By: Relevance
“…In studies published to date, diffused optical tomography and diffused optical spectroscopy have demonstrated the potential for predicting breast cancer pathological response. Studies have shown that accurate predictions were made in the neoadjuvant setting by utilizing pretreatment hemoglobin levels or blood oxygen saturations (SO 2 ) [ 20 , 21 , 23 , 31 ], or by monitoring early changes of hemoglobin content and SO 2 at 1 day or 1 week [ 19 , 27 ], or after the first two cycles of NAC [ 20 , 22 , 23 ]. In this study, we have developed prediction models and have shown that the best pretreatment predictors are HER2 and tHb (AUC = 0.88).…”
Section: Discussionmentioning
confidence: 99%
“…In studies published to date, diffused optical tomography and diffused optical spectroscopy have demonstrated the potential for predicting breast cancer pathological response. Studies have shown that accurate predictions were made in the neoadjuvant setting by utilizing pretreatment hemoglobin levels or blood oxygen saturations (SO 2 ) [ 20 , 21 , 23 , 31 ], or by monitoring early changes of hemoglobin content and SO 2 at 1 day or 1 week [ 19 , 27 ], or after the first two cycles of NAC [ 20 , 22 , 23 ]. In this study, we have developed prediction models and have shown that the best pretreatment predictors are HER2 and tHb (AUC = 0.88).…”
Section: Discussionmentioning
confidence: 99%
“…The 20 mm × 30 mm × 20 mm ellipsoidal tumor was investigated at depths varying from 0 to 10 mm between the surface of the tissue (i.e., skin) and top surface of the tumor. This represents a typical range of palpable breast tumor depths studied with reflectance-based DOI [35]. The source and detector geometry represents the manual translation of a simple single source-detector separation (SDS) probe with a separation of 28 mm over a 1 cm spaced rectangular 2D grid pattern [5], similar to that used in the ACRIN 6691 multicenter trial of diffuse optical spectroscopy in breast cancer therapy [36].…”
Section: Simulation Overviewmentioning
confidence: 99%
“…Many prior studies have utilized FD-DOI or TD-DOI to obtain absolute concentrations of , HHb, , and lipid content at baseline and time points leading up to the midpoint of NAC. 7 13 These studies have generally found that decreases in HHb and and an increase in lipid at various time points between 1 week and midpoint of chemotherapy (compared to baseline) are well correlated with a pathologic complete response (pCR). One of these studies even showed statistically significant optical contrast in between responders and nonresponders as early as 1 day into chemotherapy.…”
Section: Introductionmentioning
confidence: 99%